From mouse to man: safety, immunogenicity and efficacy of a candidate leishmaniasis vaccine LEISH‐F3+GLA‐SE. Issue 4 (10th April 2015) - Coler, Rhea N; Duthie, Malcolm S; Hofmeyer, Kimberly A; Guderian, Jeffery; Jayashankar, Lakshmi; Vergara, Julie; Rolf, Tom; Misquith, Ayesha; Laurance, John D; Raman, Vanitha S; Bailor, H Remy; Cauwelaert, Natasha Dubois; et al.
Abstract : Key antigens of Leishmania species identified in the context of host responses in Leishmania ‐exposed individuals from disease‐endemic areas were prioritized for the development of a subunit vaccine against visceral leishmaniasis (VL), the most deadly form of leishmaniasis. Two Leishmania proteins—nucleoside hydrolase and a sterol 24‐c‐methyltransferase, each of which are protective in animal models of VL when properly adjuvanted— were produced as a single recombinant fusion protein NS (LEISH‐F3) for ease of antigen production and broad coverage of a heterogeneous major histocompatibility complex population. When formulated with glucopyranosyl lipid A‐stable oil‐in‐water nanoemulsion (GLA‐SE), a Toll‐like receptor 4 TH 1 (T helper 1) promoting nanoemulsion adjuvant, the LEISH‐F3 polyprotein induced potent protection against both L. donovani and L. infantum in mice, measured as significant reductions in liver parasite burdens. A robust immune response to each component of the vaccine with polyfunctional CD4 TH 1 cell responses characterized by production of antigen‐specific interferon‐γ, tumor necrosis factor and interleukin‐2 (IL‐2), and low levels of IL‐5 and IL‐10 was induced in immunized mice. We also demonstrate that CD4 T cells, but not CD8 T cells, are sufficient for protection against L. donovani infection in immunized mice. Based on the sum of preclinical data, we prepared GMP materials and performed a phase 1 clinical study with LEISH‐F3+GLA‐SE in healthy, uninfected adults in the United States. The vaccine candidate was shown to be safe and induced a strong antigen‐specific immune response, as evidenced by cytokine and immunoglobulin subclass data. These data provide a strong rationale for additional trials in Leishmania ‐endemic countries in populations vulnerable to VL. Leishmaniasis: Two‐protein vaccine provides promising protection: A vaccine developed against the deadliest form of leishmaniasis is protective in mice and provokes a robust human immune response. Two different species of the sandfly‐borne Leishmania parasite cause visceral leishmaniasis (VL), a potentially lethal disease that affects 200–400, 000 people annually. The efficacy of existing drugs is dwindling, but researchers led by Rhea Coler at the Infectious Disease Research Institute in Seattle, USA, have devised a promising vaccine candidate based on two parasite proteins. The vaccine stimulated a potent immune response in mice, and this response protected against disease by both the parasite species associated with VL. The researchers subsequently vaccinated 36 healthy human volunteers, and showed that the candidate vaccine was safe and induced an immune response against the appropriate parasite proteins, clearing the way for early‐stage clinical trials.